Double-balloon enteroscopy for ERCP in patients with Billroth II anatomy: results of a large series of papillary large-balloon dilation for biliary stone removal - Cheng, Chi-Liang; Liu, Nai-Jen; Tang, Jui-Hsiang; Yu, Ming-Chin; Tsui, Yi-Ning; Hsu, Fang-Yu; Lee, Ching-Song; Lin, Cheng-Hui (Endoscopy International Open, 2015)
Background and study aims: Data on double-balloon enteroscopy (DBE)-assisted endoscopic retrograde cholangiopancreatogrphy (ERCP) in patients with Billroth II gastrectomy and the use of endoscopic papillary large-balloon dilation (EPLBD) for the removal of common bile duct stones in Billroth II anatomy are limited. The aims of the study were to evaluate the success of DBE-assisted ERCP in patients with Billroth II gastrectomy and examine the efficacy of EPLBD ( ≥ 10 mm) for the removal of common bile duct stones.Patients and methods: A total of 77 patients with Billroth II gastrectomy in whom standard ERCP had failed underwent DBE-assisted ERCP. DBE success was defined as visualizing the papilla and ERCP success as completing the intended intervention. The clinical results of EPLBD for the removal of common bile duct stones were analyzed.Results: DBE was successful in 73 of 77 patients (95 %), and ERCP success was achieved in 67 of these 73 (92 %). Therefore, the rate of successful DBE-assisted ERCP was 87 % (67 of a total of 77 patients). The reasons for ERCP failure (n = 10) included tumor obstruction (n = 2), adhesion obstruction (n = 2), failed cannulation (n = 3), failed stone removal (n = 2), and bowel perforation (n = 1). Overall DBE-assisted ERCP complications occurred in 5 of 77 patients (6.5 %). A total of 48 patients (34 male, mean age 75.5 years) with common bile duct stones underwent EPLBD. Complete stone removal in the first session was accomplished in 36 patients (75 %); mechanical lithotripsy was required in 1 patient. EPLBD-related mild perforation occurred in 2 patients (4 %). No acute pancreatitis occurred.Conclusions: DBE permits therapeutic ERCP in patients who have a difficult Billroth II gastrectomy with a high success rate and acceptable complication rates. EPLBD is effective and safe for the removal of common bile duct stones in patients with Billroth II anatomy.